2013
DOI: 10.3109/00016489.2013.800228
|View full text |Cite
|
Sign up to set email alerts
|

Impact of head and neck malignancies on risk factors and survival in systemic lupus erythematosus

Abstract: We found a 2.16-fold higher risk of HNMs in patients diagnosed with SLE compared with the risk of first malignancy in the age-matched controls (incidence rate ratio, IRR = 2.16, p < 0.05). The site with the highest incidence of HNMs in SLE patients was the oral cavity (5/11, 45.45%), followed by the nasopharynx (4/11, 36.36%). SLE displayed no synergic effect on the survival of SLE patients with an HNM compared with age-matched controls with a new HNM (p = 0.2446).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…SLE patients are at increased risk of other types of malignancy including head and neck, thyroid and liver. (Table 1) A recent study [84] reported a SIR for head and neck cancers of 2.16 (95% CI, 1.13-4.13) in SLE, consistent with previous data. [17] However, both of these studies were in Asian populations (which have a higher general population risk for head and neck malignancy), therefore the relevance of these data to North American and European SLE populations is uncertain.…”
Section: Other Cancers With Increased Risksupporting
confidence: 89%
“…SLE patients are at increased risk of other types of malignancy including head and neck, thyroid and liver. (Table 1) A recent study [84] reported a SIR for head and neck cancers of 2.16 (95% CI, 1.13-4.13) in SLE, consistent with previous data. [17] However, both of these studies were in Asian populations (which have a higher general population risk for head and neck malignancy), therefore the relevance of these data to North American and European SLE populations is uncertain.…”
Section: Other Cancers With Increased Risksupporting
confidence: 89%
“…Several individual cohort studies have reported that the risk of non-hematologic malignancies such as lung [1-3, 5, 6, 9, 33], liver [2-4, 6, 34], head and neck [3, 5, 10], thyroid [1-3, 35], vaginal/vulvar [1-4, 6], cervical (cancerous and pre-cancerous) [3, 4, 7, 12, 13, 36-42], dermatologic [3-5, 19], bladder or renal [2-4, 14, 43], anal [4, 13], and pancreatic [3, 13] are also increased in SLE.…”
Section: Malignancy Risk In Adult Slementioning
confidence: 99%
“…Chang et al [10] in a study involving 8,751 Taiwanese patients with SLE reported an incidence rate ratio (IRR) of 2.16 (1.13–4.13) for head and neck malignancies. The incidence of head and neck cancers was highest in the oral cavity (5 of 11 cancers, 45.45%) followed by the nasopharynx (4 of 11, 36.36%).…”
Section: Malignancy Risk In Adult Slementioning
confidence: 99%
See 1 more Smart Citation
“…Specific Autoimmune (AI) diseases have also been associated with predisposing individuals to and increasing cancer risk as seen in a broad review [8] . A myriad of studies that included oral cancer patients saw an increased risk of oral malignancies due to the presence of AI disease, while a few dissented and contradicted those findings [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%